2015
DOI: 10.1074/jbc.m114.623058
|View full text |Cite
|
Sign up to set email alerts
|

Regulated in Development and DNA Damage 1 Is Necessary for Hyperglycemia-induced Vascular Endothelial Growth Factor Expression in the Retina of Diabetic Rodents

Abstract: Background: VEGF plays a causal role in diabetic retinopathy. Results: Hyperglycemia induced VEGF and REDD1 expression in the retina of wild-type, but not REDD1 knock-out mice. Conclusion: REDD1 is necessary for hyperglycemia mediated effects on VEGF expression in the retina of diabetic mice. Significance: Molecular therapies targeting REDD1 could prove useful in preventing pathological effects of hyperglycemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
57
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(68 citation statements)
references
References 52 publications
10
57
0
1
Order By: Relevance
“…GAM attenuated insulin-induced phosphorylation of the mTORC1 substrates p70S6K1 and 4E-BP1 (Fig 1D). We previously demonstrated a similar attenuation of mTORC1 substrate phosphorylation in TR-MUL cells in response to hyperglycemic conditions (13). Notably, the repressive effect of GAM was independent of the glucose concentration in the cell culture medium (Fig 1E).…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…GAM attenuated insulin-induced phosphorylation of the mTORC1 substrates p70S6K1 and 4E-BP1 (Fig 1D). We previously demonstrated a similar attenuation of mTORC1 substrate phosphorylation in TR-MUL cells in response to hyperglycemic conditions (13). Notably, the repressive effect of GAM was independent of the glucose concentration in the cell culture medium (Fig 1E).…”
Section: Resultsmentioning
confidence: 62%
“…Furthermore, they are responsible for the synthesis and secretion of a number of hormones, such as the pro-angiogenic cytokine vascular endothelial growth factor (VEGF), that play an essential and causative role in retinal vascular complications (12). Our laboratory recently demonstrated that inhibition of the mTORC1 signaling pathway contributes to Müller cell derived synthesis of VEGF in response to diabetes (13). A key regulator of this effect is the translational repressor 4E-BP1.…”
Section: Introductionmentioning
confidence: 99%
“…Mice were anesthetized by isoflurane inhalation 16 h after the previous feeding to control for acute effects of diet. Retinas were flash-frozen in liquid nitrogen, and lysates were prepared as previously described (47). Protein concentrations were assessed by the Bradford assay, and supernatants were combined with a 2ϫ Laemmli buffer, boiled for 5 min, and analyzed via Western blotting.…”
Section: Methodsmentioning
confidence: 99%
“…VEGF is produced by differentiated human RPE cells in vitro and in vivo and also involved in paracrine signaling between the RPE and the CC [40]. Hyperglycemia has been reported to induce the level of VEGF in the retina [41], RPE [42] and retinal endothelial cells [43]. Also, an increased level of VEGF mRNA in retina has been detected in DR and ROP [44].…”
Section: Discussionmentioning
confidence: 99%